One-stage nipple and breast reconstruction using a deep inferior epigastric perforator flap after a skin-sparing mastectomy - Hyun Jun Cho; Hyo Jeong Kwon; Suk-Ho Moon; Young Joon Jun; Jong Won Rhie; Deuk Young Oh (Archives of Plastic Surgery, 2020)
Background Nipple reconstruction is usually performed as a delayed procedure in patients with breast cancer who undergo skin-sparing mastectomy and breast reconstruction surgery using a deep inferior epigastric perforator (DIEP) flap. The authors designed this study to evaluate the utility of breast reconstruction based on a DIEP flap and immediate nipple reconstruction. Methods A retrospective review was conducted of all patients who underwent breast reconstruction performed by a single plastic surgeon from October 2016 to June 2018. Through a questionnaire and chart review, we compared surgical results and complications in cases of single-stage nipple reconstruction after skin-sparing mastectomy (n=17) with patients who underwent delayed nipple reconstruction after skin-sparing mastectomy, modified radical mastectomy, or simple mastectomy (n=7). Results In a subjective analysis using clinical photos, the immediate nipple reconstruction group had higher scores than their counterparts in an evaluation of the nipple-areolar complex (NAC) (NAC placement, 3.34 vs. 3.04; nipple projection, 3.05 vs. 3.03; nipple size, 3.30 vs. 3.29). No significant differences between the groups were found in terms of complications. Conclusions Simultaneous nipple reconstruction is a reliable surgical method with economic advantages. No differences were found in terms of outcomes and complications in comparison to delayed reconstruction. Therefore, surgeons can consider simultaneous nipple reconstruction without particular concerns about asymmetry or necrosis.